L’analyse a priori, un outil pour « penser » les ajustements didactiques en classe de mathématiques ? - Aurélie Chesnais; Lalina Coulange (Éducation et Socialisation)
In this article, we propose to show how a priori analysis, a methodological tool shared in mathematics didactics research, can contribute to "thinking" adjustment in the study of teaching practices and their impact on learning. After a brief review of the two notions of a priori analysis and adjustment, we illustrate this contribution through two examples taken from our own research on the practices of two teachers teaching in priority neighbourhoods. These examples show how a priori analysis allows the researcher to apprehend adjustment gestures in the study of teaching practices and their potentially differentiating effects on mathematics learning. The final discussion comes back to the connection made between a priori analysis and adjustment from the point of view of research in mathematics didactics, while opening up perspectives on training.